Early Maladaptive Cognitive Schemas in Child Sexual Offenders Compared with Sexual Offenders against Adults and Nonsexual Violent Offenders: An Exploratory Study. (1st May 2013) - Chakhssi, Farid; de Ruiter, Corine; Bernstein, David P.
Abstract: Introduction: Although there is a growing body of research on the role of offense supporting cognitive distortions in child sexual offending, little is known about the origins of these distortions. According to cognitive theory, maladaptive cognitive schemas originating in adverse childhood experiences with caregivers have been hypothesized to underlie these cognitive distortions. Aim: This exploratory study investigates early maladaptive schemas (EMSs) in child sexual offenders compared with sexual offenders against adults and nonsexual offenders. Main Outcome Measures: EMSs were measured with the Young Schema Questionnaire, and psychopathy was measured with the Psychopathy Checklist‐Revised. Methods: Three groups of forensic inpatients—23 child sexual offenders, 19 sexual offenders against adults, and 24 nonsexual violent offenders—were assessed. Multivariate analyses of covariance were used to examine the hypothesized group differences in EMSs. Results: Results showed that, after controlling for level of psychopathy, EMSs related to Abandonment ( M  = 2.61 vs. M  = 1.73, P  < 0.01), Social Isolation ( M  = 2.50 vs. M  = 1.62, P  < 0.01), Defectiveness/Shame ( M  = 2.05 vs. M  = 1.42, P  < 0.05), Subjugation ( M  = 2.28 vs. M  = 1.57, P  < 0.05), and Self‐Sacrifice ( M  = 3.29 vs. M  = 2.41, P  < 0.05) were more prevalent in child sexual offenders compared with nonsexual violent offenders. Compared with sexual offenders against adults, child sexual offenders showed a trend to have higher scores on EMSs related to Social Isolation ( M  = 2.50 vs. M  = 1.88, P  = 0.066). Conclusions: Our findings suggest that EMSs may play a role in offending behavior in child sexual offenders and offer the possibility of informing treatment strategies.Chakhssi F, de Ruiter C, and Bernstein DP. Early maladaptive cognitive schemas in child sexual offenders compared with sexual offenders against adults and nonsexual violent offenders: An exploratory study. J Sex Med 2013;10:2201–2210.